THE INFLUENCE OF FINANCIAL BEHAVIOR, OVERCONFIDENCE, AND RISK PERCEPTION ON INVESTMENT DECISIONS: THE ROLE OF FINANCIAL LITERACY MEDIATION (AN EMPIRICAL STUDY OF MILLENNIAL INVIDUAL INVESTORS IN JAKARTA) - Yanti, Feby (International Journal of Social Service and Research, 2024)
This study aims to test and analyze the influence of financial behavior, overconfidence, and risk perception on financial literacy and investment decisions in the millennial generation in Jakarta. This study was conducted using quantitative methods, structural equation modeling (SEM), and assisted by the Smart PLS 4.0 program with a total of 100 respondents with an average age of 25-35 years. The structural model was evaluated using R-square for dependent constructs, Stone-Geisser Q-square test for Q2 predictive relevance, and significance test of structural path parameter coefficients. The results of this study can be an input in the development of investment behavior theory, especially investment decision-making, as well as the mediation role of financial literacy in these relationships, on individual millennial investors in the Jakarta area. The study found that financial behavior and overconfidence significantly impact the financial literacy of the Millennial Generation in Jakarta, while overconfidence did not. It is recommended that Millennial investors focus on improving their financial literacy, risk perception, and financial behavior to influence investment decisions, while avoiding overconfidence.